Advanced steels : the recent scenario in steel science and technology (Beijing : Metallurgical Industry Press, 2011)
"Advanced Steels: The Recent Scenario in Steel Science and Technology" contains more than 50 articles selected from the proceedings of the International Conference on Advanced Steels (ICAS) held during 9-11, Nov, 2010 in Guilin, China. This book covers almost all important aspects of steels from physical metallurgy, steel grades, processing and fabrication, simulation, to properties and applications. The book is intended for researchers and postgraduate students in the field of steels, metallurgy and materials science. Prof. Yuqing Weng is an academician of Chinese Academy of Engineering and the president of The Chinese Society for Metals. Prof. Han Dong is the vice president of Central Iron & Steel Research Institute and the director of National Engineering Research Center of Advanced Steel Technology, China. Prof. Yong Gan is an academician of Chinese Academy of Engineering, the vice president of Chinese Academy of Engineering and the president of Central Iron & Steel Research Institute, China.
También disponible en formato EPUB